KONTRIBUSI ARTIFICIAL INTELLIGENCE DALAM RESTRUKTURISASI PROSES KERJA KANTORAN: STUDI LITERATUR TENTANG INOVASI TEKNOLOGI DI DUNIA KERJA - Khairani Shafira; Mardani Supranata (Bajang Institute, 2025)
This study explores the adoption of Artificial Intelligence (AI) in office work environments in Indonesia and its impact on operational efficiency, productivity, and employee roles. AI, which includes the automation of administrative tasks and data analysis for decision-making, is transforming traditional work methods. The study aims to explore how AI implementation can enhance organizational performance, along with the challenges that arise during the digital transformation process. Through literature review and case study analysis, the research finds that employees' digital literacy plays a crucial role in the effectiveness of AI adoption. Additionally, the use of AI in recruitment influences candidates' perceptions of the organization. However, the study also identifies psychological impacts on employees, such as job anxiety and professional identity confusion. The policy and managerial implications highlight the need for strong regulations, continuous training, and careful change management. This research is expected to contribute to the development of more inclusive and ethical AI implementation strategies in office work environments in Indonesia.